Konstruksi Sosial Pemberitaan Kasus Simulator SIM di Media Online Kompas.com - Kresno, Slamet Dodi (Universitas Semarang, 2014)
This is a descriptive study using a qualitative approach. The method used in this research is to use the model of Robert framing. N.Entman. This model is used to determine how the mass media to construct reality with four elements: define problems, diagnose causes, make moral judgments and treatment recommendation. The method used is qualitative research and analysis of framing. The research was conducted by collecting data from websites related cases sim simulator. Results showed that online media news Kompas.com construct simulator sim case based on two issues will find that one of the suspectsis a police officer Inspector General Djoko Susilo abuse of power and authority toenrich them selves and others and relationships with the Police Commissionis getting better.